The Effects of Problem-Based, Project-Based, and Case-Based Learning on Students’ Motivation: a Meta-Analysis - Wijnia, Lisette; Noordzij, Gera; Arends, Lidia R.; Rikers, Remigius M. J. P.; Loyens, Sofie M. M. (Educational psychology review, 2024)
In this meta-analysis, we examined the effects on students’ motivation of student-centered, problem-driven learning methods compared to teacher-centered/lecture-based learning. Specifically, we considered problem-based (PBL), project-based (PjBL), and case-based learning (CBL). We viewed motivation as a multifaceted construct consisting of students’ beliefs (competence and control beliefs), perceptions of task value (interest and importance), and reasons for engaging in tasks (intrinsic or extrinsic). In addition, we included students’ attitudes toward school subjects (e.g., science). We included 139 subsamples from the 132 included reports (83 PBL, 37 PjBL, and 19 CBL subsamples). Overall, PBL, PjBL, and CBL had a small to moderate, heterogeneous positive effect ( d = 0.498) on motivation. Moderator analyses revealed that larger effect sizes were found for students’ beliefs, values, and attitudes compared to students’ reasons for studying. No differences were found between the three instructional methods on motivation. However, effect sizes were larger when problem-driven learning was applied in a single course (when compared to a curriculum-level approach). Larger effects were also found in some academic domains (i.e., healthcare and STEM) than in others. While the impact of problem-driven learning on motivation is generally positive, the intricate interplay of factors such as academic domain and implementation level underscores the need for a nuanced approach to leveraging these instructional methods effectively with regard to increasing student motivation.